2003
DOI: 10.1136/bmj.327.7421.967
|View full text |Cite
|
Sign up to set email alerts
|

Whispered voice test for screening for hearing impairment in adults and children: systematic review

Abstract: Objective To determine the accuracy of the whispered voice test in detecting hearing impairment in adults and children. Design Systematic review of studies of test accuracy. Data sources Medline, Embase, Science Citation Index, unpublished theses, manual searching of bibliographies of known primary and review articles, and contact with authors. Study selection Two reviewers independently selected and extracted data on study characteristics, quality, and accuracy of studies. Studies were included if they had cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0
13

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(114 citation statements)
references
References 19 publications
0
101
0
13
Order By: Relevance
“…The PPI data of three subjects were rejected because no distinct startle reaction could be elicited (nonresponders, mean startle amplitude on pulse-alone trials o10 mV in the presentation block relevant for %PPI calculation) and four subjects declined to continue electrophysiological recordings after completing the PPI assessment, thus resulting in 19 complete datasets (PPI, P50, CANTAB), with only PPI and CANTAB data from four subjects, and only P50 and CANTAB data from three subjects. Hearing was evaluated in all subjects, using a standard computerized whispered voice test (for a review, see Pirozzo et al, 2003). No subjects were excluded due to hearing difficulties.…”
Section: Subjectsmentioning
confidence: 99%
“…The PPI data of three subjects were rejected because no distinct startle reaction could be elicited (nonresponders, mean startle amplitude on pulse-alone trials o10 mV in the presentation block relevant for %PPI calculation) and four subjects declined to continue electrophysiological recordings after completing the PPI assessment, thus resulting in 19 complete datasets (PPI, P50, CANTAB), with only PPI and CANTAB data from four subjects, and only P50 and CANTAB data from three subjects. Hearing was evaluated in all subjects, using a standard computerized whispered voice test (for a review, see Pirozzo et al, 2003). No subjects were excluded due to hearing difficulties.…”
Section: Subjectsmentioning
confidence: 99%
“…loudness of the whisper, and the most appropriate use of letters, numbers or words for testing and tester). Modified from Pirozzo et al (2003), Table 2.…”
Section: Pirozzo and Colleagues (2003)mentioning
confidence: 99%
“…It is unclear how systematically the authors of the New Zealand report identified the evidence for OME screen test accuracy. 47 This review aimed to assess the accuracy (performance) of the whispered voice test for screening for hearing impairment in adults and children. 47 The quality of the review was judged to be moderate as no details of the selection of studies were provided.…”
Section: New Zealand Health Technology Assessmentmentioning
confidence: 99%
“…Moreover, it is known to have low sensitivity and specificity. 3 Pure tone audiometry is an ideal tool for assessment of hearing. However due to its high operating cost, requirement of trained manpower and expensive infrastructure it may not be ideal as a screening test for hearing.…”
Section: Discussionmentioning
confidence: 99%
“…It lacks reproducibility, accuracy and a standard technique. 3 The ‗Gold standard' for hearing assessment is pure tone audiometry (PTA). However, the equipment is costly; moreover it requires trained manpower and expensive infrastructure to conduct the test.…”
Section: Introductionmentioning
confidence: 99%